PENGARUH SISTEM ZONASI TERHADAP KARAKTER DAN MOTIVASI BELAJAR SISWA KELAS XI IPS 1 SMAN 1 SUNGAI TARAB - Wahyuli, Fauziah; Melia, Yenni; Yatim, Yenita (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This research started with the many problems in the implementation of the zoning system in PPDB reaping pros and cons for students, students felt that this zoning system could not provide opportunities for students to choose schools according to what they wanted, especially for students who were not able to choose schools. what they want, so that this has an impact on the character of students who excel in learning. The purpose of this research is to describe the impact of new student acceptance (ppdb) through the zoning system on the character of high achieving students (Study at SMAN 1 Sungai Tarab).The theory used in this study is social cognitive theory developed by Albert Bandura. This research is a qualitative research using descriptive method. Data collection methods are through interviews and observation. Interviews were conducted with 13 informants, the informants in this study were taken using a purposive sampling technique. The data analysis model is through the stages of data collection, data reduction, data presentation and drawing conclusions.From the results of the research it was revealed that the impact on students who excel is more on the negative impact because of the changes experienced by students who excel. The impacts can be described as follows: a) Changes in the character of discipline. This is shown from the attitude of students when studying, not being disciplined in obeying school rules, not being disciplined in doing assignments and students like to violate school rules. b) Changes in the character of social care, namely students who achieve more often close themselves and rarely interact more intimately with friends in their class. This is due to the feeling of disappointment that students have with this zoning policy. Students feel that their freedom in choosing a school even though they have good academic grades is hindered and limited. c) Changes in the character of student responsibility and student honesty in learning. During study students are not disciplined and do not have a sense of responsibility for the tasks or exercises they are doing. Students are not honest in doing the tasks given by the teacher. So it can be concluded that the implementation of PPDB through the zoning system has many negative impacts on the character of high achieving students at SMAN 1 Sungai Tarab.Key words: PPDB, Zoning, Character